2008
DOI: 10.1074/jbc.m804268200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of UCP1 and the Glycerol Phosphate Cycle Synergistically Increases Energy Expenditure to Resist Diet-induced Obesity

Abstract: Our current paradigm for obesity assumes that reduced thermogenic capacity increases susceptibility to obesity, whereas enhanced thermogenic capacity protects against obesity. Here we report that elimination of two major thermogenic pathways encoded by the mitochondrial uncoupling protein (Ucp1) and mitochondrial glycerol-3-phosphate dehydrogenase (Gdm) result in mice with increased resistance to diet-induced obesity when housed at 28°C, provided prior adaptation occurred at 20°C. Obesity resistant Gdm ؊/؊ ⅐Uc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 53 publications
5
76
0
Order By: Relevance
“…A large body of literature links increased dietary fat intake with obesity and cancer progression [59], but it is becoming clear that factors affecting obesity are altered at ST. For example, a UCP-1 knockout mouse model showed deficits in coldinduced non-shivering thermogenesis as expected, but failed to develop the expected obesity phenotype [60,61]. Several groups have now shown that this unexpected lack of the predicted phenotype was because the mice were housed at ST, and when these mice are housed at TT (and are not burning energy through adaptive thermogenesis) they do become obese [61][62][63][64]. This effect of ST on obesity has been observed in other models as well [65][66][67], and it is clear that precise data on the linkage between diet, obesity, and cancer should be re-examined in the context of absence of cold stress.…”
Section: Being Too Cold Can Be Helpful In Diseases In Which Immunosupmentioning
confidence: 84%
“…A large body of literature links increased dietary fat intake with obesity and cancer progression [59], but it is becoming clear that factors affecting obesity are altered at ST. For example, a UCP-1 knockout mouse model showed deficits in coldinduced non-shivering thermogenesis as expected, but failed to develop the expected obesity phenotype [60,61]. Several groups have now shown that this unexpected lack of the predicted phenotype was because the mice were housed at ST, and when these mice are housed at TT (and are not burning energy through adaptive thermogenesis) they do become obese [61][62][63][64]. This effect of ST on obesity has been observed in other models as well [65][66][67], and it is clear that precise data on the linkage between diet, obesity, and cancer should be re-examined in the context of absence of cold stress.…”
Section: Being Too Cold Can Be Helpful In Diseases In Which Immunosupmentioning
confidence: 84%
“…One reason for its limited expression is the energy loss resulting from the conversion of NADH to FADH 2 ; this energy is converted into heat [64]. The energy loss has been suggested to allow this shuttle to transfer electrons against an unfavourable electron gradient, i.e.…”
Section: Figure 8 Gsis From Mouse Islets Is Unaffected By Phs Whereamentioning
confidence: 99%
“…In contrast, activity in the malate-aspartate shuttle does not result in any loss of energy. In brown adipose tissue, a high rate of fuel oxidation is required to generate heat [64]. Likewise, in the β-cell, the glycerol phosphate shuttle allows a high glycolytic rate even in situations when the mitochondrial redox potential is very high; this would extend the range of glucose concentrations at which insulin can be concentration-dependently secreted.…”
Section: Figure 8 Gsis From Mouse Islets Is Unaffected By Phs Whereamentioning
confidence: 99%
“…However, it was also demonstrated that a lean phenotype could be induced in mice by augmenting energy expenditure in white adipocytes in the absence of UCP1, by (1) mitochondrial uncoupling elicited by increased intracellular levels of free fatty acids (Maassen et al 2007;Yehuda-Shnaidman et al 2010), (2) futile cycling between fatty acid synthesis and re-esterification (Ribet et al 2010), or (3) other mechanisms (Granneman et al 2003;Ukropec et al 2006;Anunciado-Koza et al 2008). In this respect, 15-deoxy-delta 12,15-prostaglandin J2, an anti-inflammatory mediator and potent endogenous PPARc agonist (Forman et al 1995;Kliewer et al 1995), that is, endogenous analog of TZD was synergistically induced in response to the combination treatment using n-3 polyunsaturated fatty acids and calorie restriction in association with stimulation of mitochondrial biogenesis and fatty acid oxidation in WAT in the absence of UCP1 (Flachs et al 2011).…”
Section: Treatments Enhancing Energy Expenditurementioning
confidence: 99%